Unveiling the Marketing Tactics of Indonesian Fundamentalist Group: A Delphi Method Analysis - Karamoy, Arindra Khrisna; Meliala, Adrianus (UI Scholars Hub, 2025)
This study investigated whether Indonesian fundamentalist group utilizes marketing principles for recruitment. The research employed a Delphi method, gathering expert consensus from marketing, communication, and visual communication fields to assess the group's use of marketing strategies in attracting sympathizers and disseminating their ideology. The first round demonstrated complete agreement on the use of marketing principles. The second round revealed some disagreement regarding the classification of mosques as distribution channels, suggesting a nuanced application focusing more on promotion than traditional marketing models. The findings highlight sophisticated marketing techniques used by this group, emphasizing the need for further investigation into how such groups leverage marketing for influence. This includes exploring the broader application of marketing principles in radicalization, connections to popular culture, and developing effective counter-narratives using social marketing. Understanding these strategies is crucial for developing counter-measures and promoting social cohesion. The study's results underscore the importance of examining how religious groups employ marketing strategies, particularly in contexts lacking prior research.